Grafting-enhanced tolerance of cucumber to toxic stress is associated with regulation of phenolic and other aromatic acids metabolism - Xiao,Xuemei; Li,Ju; Lyu,Jian; Hu,Linli; Wu,Yue; Tang,Zhongqi; Yu,Jihua; Calderón-Urrea,Alejandro (PeerJ, 2022)
Toxic stress caused by autotoxins is a common phenomenon for cucumber under monoculture condition. A previous study demonstrated that grafting could enhance the resistance of cucumber to cinnamic acid (CA) stress, but the underlying mechanism behind this enhanced resistance is still unclear. In the present study, we reconfirmed the stronger resistance of grafted rootstock (RG) compared to the non-grafted (NG) cucumber as measured though plant biomass accumulation. In addition, we focused on the phenolic and other aromatic acids metabolism in hydroponic culture model system using a combination of qRT-PCR (to measure gene expression of relevant genes) and HPLC (to detect the presence of phenolic and other aromatic acids). The results showed that the exogenous CA lead to the expression of four enzymes involved in phenolic and other aromatic acids biosynthesis, and a larger increase was observed in grafted rootstock (RG). Specifically, expression of six genes, involved in phenolic and other aromatic acids biosynthesis (PAL, PAL1, C4H, 4CL1, 4CL2 and COMT), with the exception of 4CL2, were significantly up-regulated in RG but down-regulated in NG when exposed to CA. Furthermore, six kinds of phenolic and other aromatic acids were detected in leaves and roots of NG and RG cucumber, while only benzoic acid and cinnamic acid were detected in root exudate of all samples. The CA treatment resulted in an increase of p-hydroxybenzonic acid, benzoic acid and cinnamic acid contents in RG cucumber, but decrease of p-coumaric acid and sinapic acid contents in NG cucumber. Surprisingly, the type and amount of phenolic and other aromatic acids in root exudate was improved by exogenous CA, particularly for RG cucumber. These results suggest that a possible mechanism for the stronger resistance to CA of RG than NG cucumber could involve the up-regulation of key genes involved in phenolic and other aromatic acids metabolism, and that the excessive phenolic compounds released to surroundings is a result of the accumulation of phenolic compounds in a short time by the plant under stress.
Keywords: Cucumber; Grafting; Cinnamic acid; Phenolic and other aromatic acids biosynthesis